2014
DOI: 10.1002/app.41612
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a small amount of sulfur on the physical and mechanical properties of peroxide‐cured fully saturated HNBR compounds

Abstract: Sulfur can be used as crosslink coagent in unsaturated elastomer. In this work, a fully saturated HNBR with 39 wt % nitrile content was selected to investigate the effect of a small amount of sulfur acting as crosslink coagent on the physical and mechanical properties of peroxide-cured vulcanizates. First, selective cleavage of polysulfide (ASxA) and monosulfide(ASA) bond by combined thiol-piperidine treatment were performed and the existence of poly/monosulfide bond in sulfur-contained HNBR compounds was veri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…However, few work has been done to study the effect of sulfur or sulfur donors as coagent on network structure and on the cyclic–dynamic fatigue properties of peroxide cured rubbers. Sheng studied the effect of sulfur as the coagent on the properties of peroxide cured hydrogenated NBR and the results showed that small amount of sulfur could impart the peroxide vulcanizates some “sulfide properties” like dynamic property, tensile strength.…”
Section: Introductionmentioning
confidence: 99%
“…However, few work has been done to study the effect of sulfur or sulfur donors as coagent on network structure and on the cyclic–dynamic fatigue properties of peroxide cured rubbers. Sheng studied the effect of sulfur as the coagent on the properties of peroxide cured hydrogenated NBR and the results showed that small amount of sulfur could impart the peroxide vulcanizates some “sulfide properties” like dynamic property, tensile strength.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are also some disadvantages compared to sulfurcured systems, as low scorch safety and worse dynamic and elastic properties of vulcanizates. 7,8 As the cross-linking efficiency of peroxides is sometimes rather low, the so-called coagents are often introduced to boost peroxide vulcanization. 9,10 Coagents are mostly polar vinyl monomers with high affinity toward free radicals and readily graft to macromolecular chains to form a complex cross-linked network.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the cross-link bonds in HNBR vulcanizates cured by S are mainly polysulfide (C-S x -C, x > 2) bonds, and C-S-C bonds are formed in the S donor system, while C-C bonds occur in the peroxide system. 25 Different cross-link structure and cross-link bonds formed in the HNBR vulcanizates are shown in Figure 1. Among three kinds of the cross-link bonds, the sequence of the bond energy is as follows: C-C (peroxide) > C-S-C (S donor) > C-S x -C (S).…”
Section: Cross-link Structure and Cross-link Densitymentioning
confidence: 99%